Determination of the coordinate dependence of a pinning potential from the microwave experiment with vortices - Shklovskij, V.A.; Dobrovolskiy, O.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
The measurement of the complex impedance response and accompanied power absorption P(ω) in the radiofrequency and microwave ranges represents a most popular experimental method to investigate pinning mechanismsand the vortex dynamics in type-II superconductors. In the theory, the pinning potential (PP) well for a vortexmust be a priori specified in order to subsequently analyze the measured data. We have theoretically solved the inverse problem at T = 0 K and exemplify how the coordinate dependence of a PP can be determined from a set of experimental curves P(ω|j0) measured at subcritical dc currents 0 < j0 < jc under a small microwave excitation j1 << jc with frequency ω. We furthermore elucidate how and why the depinning frequency ωp, which separatesthe non-dissipative (quasi-adiabatic) and the dissipative (high-frequency) regimes of small vortex oscillationsin the PP, is reduced with the increase of j0. The results can be directly applied to a wide range of conventional superconductors with a PP subjected to superimposed dc and small microwave ac currents at T << Tc.